2021
DOI: 10.47391/jpma.1247
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and anxiety symptoms in Pakistani adolescents: a study of compounded directions

Abstract: Objectives: There is an empirical evidence that symptoms of internalizing disorders such as alexithymia and anxiety increase in adolescence and these symptoms varies across gender and age groups. The purpose of this study was to explore these differences in adolescents. Method: In this cross-sectional study conducted since November 2018 to March 2019, the sample of 185 adolescents selected through random sampling method from different schools. They were assessed on alexithymia and anxiety symptoms by administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Our findings demonstrate a higher risk for alexithymia among male patients, aligning with van't Wout et al's study on 43 schizophrenia patients (van't Wout et al, 2007). This result was echoed in studies of adolescents (Jafar et al, 2021), the general population (Lane et al, 1998; Li et al, 2022), and outpatients with alcohol use disorder (Thorberg et al, 2020). The higher risk of alexithymia in male patients might be explained as follows.…”
Section: Discussionmentioning
confidence: 95%
“…Our findings demonstrate a higher risk for alexithymia among male patients, aligning with van't Wout et al's study on 43 schizophrenia patients (van't Wout et al, 2007). This result was echoed in studies of adolescents (Jafar et al, 2021), the general population (Lane et al, 1998; Li et al, 2022), and outpatients with alcohol use disorder (Thorberg et al, 2020). The higher risk of alexithymia in male patients might be explained as follows.…”
Section: Discussionmentioning
confidence: 95%
“…Alexithymia contributes ANX to 28%; Liss et al [45] found that ease of excitation interacted with difficulty identifying feelings, which may predict anxiety; if being both easily excited by stimuli and unable to identify personal feelings is particularly anxiety-provoking, alexithymia affects anxiety, and Jafar et al [46] found that by applying multiple analysis, direct and interactive effects of age groups and gender on alexithymia and anxiety symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…, F(46,3) = 130, p = .000 .-Alexithymia Predicted with (OC) with a positive correlation , R2 = .141, F(20,9) = 129, p = .000 . -Alexithymia Predicted with (INS) with a positive correlation , R2 = .173, F(26,5) = 128, p = .000 .…”
mentioning
confidence: 93%
“…Numerous studies have evaluated anxiety and depressive disorders in the general population and have demonstrated a relationship with alexithymia [6][7][8][9][10][11]. Alexithymia refers to a deficit in the ability to recognize and express emotions, use of concrete speech and thoughts related to external events, and a paucity of notional thought processes [12].…”
Section: Introductionmentioning
confidence: 99%